The influence of brand ambassadors and brand image on the intention to buy food products - Dede Suleman; Yulia Nur Hasanah; Sabil Sabil; Devy Sofyanty; Rachmat Sjarief; Fendi saputra (Junal Ilmu Manajemen, 2023)
The important role of digital era consumers in making the buying process is quite different from before. Therefore, it is necessary to do research on the effect of Brand Ambassadors and brand image on Purchase Intention to purchase frozen food. The population in this study is people who live in South Tangerang with a sampling technique in the form of purposive sampling of 120 respondents. This study uses AMOS SEM data analysis techniques. The results of this study say that brand ambassadors and brand image have an effect on consumer buying interest and brand image is the factor that has the greatest influence on consumer buying interest.